Distributed Computing and Networking 11th International Conference, ICDCN 2010, Kolkata, India, January 3-6, 2010. Proceedings - Kant, Krishna; Pemmaraju, Sriram V.; Sivalingam, Krishna M.; Wu, Jie.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 11th International Conference on Distributed Computing and Networking, ICDCN 2010, held in Kolkata, India, during January 3-6, 2010. There were 169 submissions, 96 to the networking track and 73 to the distributed computing track. After review the committee selected 23 papers for the networking and 21 for the distributed computing track. The topics addressed are network protocol and applications, fault-tolerance and security, sensor networks, distributed algorithms and optimization, peer-to-peer networks and network tracing, parallel and distributed systems, wireless networks, applications and distributed systems, optical, cellular and mobile ad hoc networks, and theory of distributed systems.
Keynotes -- An Intelligent IT Infrastructure for the Future -- Heavy Tails and Models for the Web and Social Networks -- Data Structures and Algorithms for Packet Forwarding and Classification: Prof. A.K. Choudhury Memorial Lecture -- Spoken Web: A Parallel Web for the Masses: Industry Keynote -- India$1 (Bs Mobile Revolution and the Unfinished Tasks: Invited Lecture -- Network Protocols and Applications -- Scheduling in Multi-Channel Wireless Networks -- Email Shape Analysis -- Maintaining Safety in Interdomain Routing with Hierarchical Path-Categories -- Fault-tolerance and Security -- On Communication Complexity of Secure Message Transmission in Directed Networks -- On Composability of Reliable Unicast and Broadcast -- A Leader-Free Byzantine Consensus Algorithm -- Authenticated Byzantine Generals in Dual Failure Model -- Sensor Networks -- Mission-Oriented k-Coverage in Mobile Wireless Sensor Networks -- Lessons from the Sparse Sensor Network Deployment in Rural India -- A New Architecture for Hierarchical Sensor Networks with Mobile Data Collectors -- Stability Analysis of Multi-hop Routing in Sensor Networks with Mobile Sinks -- Distributed Algorithms and Optimization -- Optimizing Distributed Computing Workflows in Heterogeneous Network Environments -- Radio Network Distributed Algorithms in the Unknown Neighborhood Model -- Probabilistic Self-stabilizing Vertex Coloring in Unidirectional Anonymous Networks -- A Token-Based Solution to the Group Mutual l-Exclusion Problem in Message Passing Distributed Systems -- Peer-to-Peer Networks and Network Tracing -- The Weak Network Tracing Problem -- Poisoning the Kad Network -- Credit Reputation Propagation: A Strategy to Curb Free-Riding in a Large BitTorrent Swarm -- Formal Understanding of the Emergence of Superpeer Networks: A Complex Network Approach -- Parallel and Distributed Systems -- Parallelization of the Lanczos Algorithm on Multi-core Platforms -- Supporting Malleability in Parallel Architectures with Dynamic CPUSETsMapping and Dynamic MPI -- Impact of Object Operations and Relationships on Concurrency Control in DOOS -- Causal Cycle Based Communication Pattern Matching -- Wireless Networks -- Channel Assignment in Virtual Cut-through Switching Based Wireless Mesh Networks -- Efficient Multi-hop Broadcasting in Wireless Networks Using k-Shortest Path Pruning -- Bandwidth Provisioning in Infrastructure-Based Wireless Networks Employing Directional Antennas -- ROTIO+: A Modified ROTIO for Nested Network Mobility -- Applications of Distributed Systems -- VirtualConnection: Opportunistic Networking for Web on Demand -- Video Surveillance with PTZ Cameras: The Problem of Maximizing Effective Monitoring Time -- DisClus: A Distributed Clustering Technique over High Resolution Satellite Data -- Performance Evaluation of a Wormhole-Routed Algorithm for Irregular Mesh NoC Interconnect -- Optical, Cellular and Mobile Ad Hoc Networks -- Dynamic Multipath Bandwidth Provisioning with Jitter, Throughput, SLA Constraints in MPLS over WDM Network -- Path Protection in Translucent WDM Optical Networks -- Post Deployment Planning of 3G Cellular Networks through Dual Homing of NodeBs -- K-Directory Community: Reliable Service Discovery in MANET -- Theory of Distributed Systems -- An Online, Derivative-Free Optimization Approach to Auto-tuning of Computing Systems -- Consistency-Driven Probabilistic Quorum System Construction for Improving Operation Availability -- Hamiltonicity of a General OTIS Network -- Specifying Fault-Tolerance Using Split Precondition Logic -- Network Protocols -- Fast BGP Convergence Following Link/Router Failure -- On Using Network Tomography for Overlay Availability -- QoSBR: A Quality Based Routing Protocol for Wireless Mesh Networks -- An ACO Based Approach for Detection of an Optimal Attack Path in a Dynamic Environment.s
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Computer system performance; Data protection; Data encryption (Computer science).; Computer software; Computer Science; Computer Communication Networks; Computer Systems Organization and Communication Networks; Data Encryption; Systems and Data Security; System Performance and Evaluation; Algorithm Analysis and Problem Complexity